Metastatic tumors in the maxillofacial region: a systematic review (Research, Society and Development, 2021)
Metastasis is a consequence of a complex biological cascade, which begins with the detachment of tumor cells from the primary site and, via blood or lymph, spread to other sites, where they form a new neoplastic colony. They represent about 1% of all malignant tumors in this region, the oral cavity being the site most affected by neoplasms. Oral and maxillofacial cancer has high morbidity and mortality rates. Thus, it is necessary that the physician and/or dental surgeon take into account metastases to this region, as, despite being a rare case, they are signs of disseminated neoplasms. Given the above, this study aimed to conduct a systematic review of the literature on the sites of the primary tumor that have metastases to the maxillofacial region, as well as the site of metastasis, the most affected gender and the most common histological type. For the construction of this article, a bibliographic survey was carried out in the SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect databases, with the help of Mendeley. The articles were collected from April to August 2021 and covered between 2010 and 2021. From a systematic review of the literature, 282 cases of metastasis to the maxillofacial region were observed. The primary sites that metastasize the most are lung, kidney, breast and liver. The most affected gender is the male and the mandible is the most affected location, followed by the gums and tongue. The most common histological type is carcinoma.